Islamic stock market and sukuk market development, economic growth, and trade openness (the case of Indonesia and Malaysia) - Harjum Muharam; Resi Junita Anwar; Robiyanto Robiyanto (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This study was conducted in order to analyse the two-way relationship between the Islamic stock market and sukuk market development, and economic growth. this study also analyses whether trade openness influences the development of the Islamic stock market and sukuk market, and economic growth. VAR (Vector Auto Regressive), VECM (Vector Error Correction Model), and a Granger Causality Test used to test the hypothesis. Using Indonesia and Malaysia as the sample countries and from February 2008 to December 2017 period, the results showed that there is a bi-directional causality between the development of the Islamic stock market and the development of the sukuk market in Indonesia and Malaysia. There is a bi-directional causality between the development of the Islamic stock market and sukuk market with economic growth in Indonesia. Unidirectional causality is found between economic growth and the sukuk market development in Malaysia. And no causality (neutrality) is reported between the development of the Islamic stock market and economic growth in Malaysia. Meanwhile, trade openness has a significant and positive effect on the sukuk market development as well as economic growth in Malaysia. For the limitations, this research only focused on two countries and only delved into the corporation sukuk market.
Keywords: G15; G19; F49; 650; Islamic stock market; Sukuk; economic growth; trade openness; VECM